Effect of Adsorption of Metal Elements Ni and V on the Structure of Humin - Yin YU; Peng XIA; Yi ZHONG; Shitan NING; Ke WANG; Jianping CHENG (Yankuang ceshi)
BACKGROUNDBlack shales are mostly developed in special periods in geological history. They not only record the evolution characteristics of paleoenvironment, paleoclimate and paleontology, but also are carriers of organic matter, oil and gas and various metal deposits. Taking the black shale of the Lower Cambrian Niutitang Formation in Guizhou as an example, it not only shows the extraordinary enrichment of V, Ni and other metal elements, forming vanadium ore and nickel-molybdenum ore, but is also rich in organic matter, with TOC content of 0.7%-14.6% (average 5.2%). At present, the co-enrichment mechanism of metal elements Ni, V and organic matter is still unclear, but organic matter plays an important role in the enrichment, migration and transformation of metal ions.OBJECTIVESTo understand the co-enrichment mechanism of organic matter and metal elements by exploring the effect of metal elements on the structure of organic matter.METHODSTake two groups of 50mL polypropylene centrifuge tubes A and B, and add 5g of humin to each centrifuge tube. Then add 20mL of Ni single element standard solution to the group A centrifuge tube, and 20mL of V single element standard solution to the group B centrifuge tube. Place the centrifuge tube in a constant temperature oscillator for 24h with the temperature of 298K and the speed of 220r/min. After standing for 24h, the filtered solid part is placed in a 50mL beaker and dried. The dried samples (numbered as HM-Ni and HM-V) and the original humin sample (numbered HM) are analyzed by element analyzer, X-ray photoelectron spectroscopy (XPS) and solid-state nuclear magnetic resonance carbon spectroscopy (13C-NMR).RESULTSThe results show that the elemental composition of humin is mainly C and O. After the action of Ni and V metal solutions, the relative contents of O and S elements in humin decrease, and the relative contents of C and N elements increase. The ratio of H/C and O/C atoms is HM>HM-V>HM-Ni. XPS test shows that the C element on the surface of humin is mainly in the form of aromatic carbon, while the O element is mainly in the form of hydroxyl oxygen. For C with different occurrence forms, the influence trend of Ni and V metal solutions on them is the same, which reduces aromatic carbon, hydroxyl carbon and carbon-based carbon, and mainly destroys aromatic carbon (C—C/C—H) single bonds. For O with different occurrence forms, the Ni metal solution reduces hydroxyl oxygen and carboxyl oxygen, which makes the hydrogen-enriched and oxygen-enriched functional groups prolapse; the V metal solution reduces carbonyl oxygen and carboxyl oxygen, which destroys the carbonyl double bond (C=O). Solid-state nuclear magnetic resonance carbon spectroscopy (13C-NMR) tests show that the action of Ni metal solution can reduce the relative contents of bridged aromatic carbon (far B), oxygen-connected aromatic carbon (far P), carbonyl carbon (fa O), methyl and quaternary carbon (fal *), as well as methylene and methine carbon (fal H); V metal solution can reduce the relative contents of protonated aromatic carbon (far H), bridged aromatic carbon (far B), oxygen-connected aromatic carbon (far P), carbonyl carbon (fa O), methyl and quaternary carbon (fal *), as well as methylene and methine carbon (fal H). Both metal solutions can make the O-enriched and H-enriched functional groups in oxygen-linked aromatic carbon (far P) and bridged aromatic carbon (far B) prolapse from the aromatic ring, shorten the lipid chain length in humin, reduce the stability of organic carbon, reduce the content of active organic carbon and reduce the degree of hydrophobicity.CONCLUSIONSThrough comparative analysis, it is shown that humin has a certain oxidation ability to Ni and V metal elements. After the action of the two metal solutions, the occurrence morphology of C and O elements in humin can be changed. Ni metal solution mainly affects the aliphatic carbon structure, while V metal solution mainly affects the aromatic carbon structure.